Comparative Anatomical Study of Kidney Differences Between the Cat and the Owl (Felis catus and Strix varia): Studi Anatomi Perbandingan Perbedaan Ginjal Antara Kucing dan Burung Hantu (Felis catus dan Strix varia) - Ahmed , Amjad Adham; Ibrahim, Thekra Atta (Procedia of Engineering and Life Science, 2025)
The aim of the present study is to investigate the anatomical variation of the morphological description of the normal kidneys of two vertebrates, the cat and the owl, which share a diet but differ in habitat. The results revealed the following: The kidney in cats is a solid, bean-like structure, reddish-brown in colour, smooth in surface, not lobed, and enclosed in a thick capsule of connective tissue. In comparison, the kidney of an owl is smooth and divided into three lobes of different sizes and shapes. It is larger in size, oblong, dark red-brown in colour, and enclosed in a thin capsule of connective tissue. The results showed that the kidneys in cats are located in the anterior region of the body cavity, below the diaphragm, and opposite the dorsal body wall, and are in pairs (right and left kidneys). In comparison, the kidneys in owls are in a symmetrical pair connected by a fibrous ligament and are located in a bony depression called the renal fossa, located in the sacral region integrated into the body cavity. Anatomical findings showed that the main blood supply to the kidneys in cats is provided by a pair of renal arteries branching from the aorta, compared to, owl kidneys receive blood from three pairs of renal arteries (anterior, middle, and posterior), which also branch from the aorta.